Non-linear dynamics of a thermomechanical pseudoelastic oscillator excited by non-ideal energy sources - Piccirillo, V.; Balthazar, J. M. [UNESP]; Tusset, A. M.; Bernardini, D.; Rega, G. (Elsevier, 2015)
This paper discusses the non-linear dynamical response of a shape-memory non-ideal oscillator. The non-ideal excitation originates from a DC electric motor with limited power supply driving an unbalanced rotating mass. The restoring force provided by the shape-memory device is described by a thermomechanical model capable of accounting for the hysteretic behavior via the evolution of a suitable internal variable. The non-linear dynamic response of the system is investigated with the voltage as control parameter. Numerical simulations show the occurrence of regular and quasi-periodic motions, which are investigated via bifurcation diagrams and phase plane portraits. The 0-1 test is used for quantitative characterization of chaotic responses. The computation of basins of attraction points out the strong dependence of the response on small changes of initial conditions, along with meaningful modifications of competing basins with variations of the control parameter. Finally, variations of the mechanical and thermal parameters of the pseudoelastic oscillator are considered, with the aim to evaluating the effects produced by the non-ideal excitation source on the non-linear dynamics of the shape memory device.
Keywords: 0-1 Test; Non-ideal systems; Nonlinear dynamics; Shape memory device; Thermomechanical coupling